Directions and policies for development of science-technology human resource in Vietnam: assessment of the past strategies and solutions for promotion in future time - Chi, Hoang Lan; Long, Hoang Xuan (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2018)
Innovation of policies for science and technology (S&T) human resource in our country passed long extended stages mainly due to missed opportunities from opened contexts, some deadlocks in policy setting practice, lacked decisive moves in realization of breakthrough solutions and orientation of innovation, and delayed works of assessment and adjustment of issued policies. For stronger promotion of innovation of policies for S&T human resource in future time, the main attentions should be oriented to certain solutions such as classification of S&T human resource for issuance of adequate policies, definition of right relations between S&T human resource and assigned tasks, and higher role of scientific leaders in R&D organizations.